The Two-Dimensional Time Frame of Common Dollar Statements. - Bailey, Andrew D.; Jensen, Daniel L. (The Accounting Review, 1977)
Common dollar financial statements add a second time dimension to financial reporing that beginning students of accounting mag find difficult to grasp. The authors find that students' difficulty in understanding the roll-forward adjustment and the distinction between monetary and nonmonetary items is alleviated when common dollar statements are introduced with a two-dimensional display. The two-dimensional display accommodates the money time dimension as distinguished from statement time, the monetary/nonmonetary distinction, the computation of income and the reconciliation of equity accounts as between statements based on common dollar magnitudes.